China’s shipping market supervision system under theRCEP: Influence, challenges and countermeasures - Shi, Yuanhong (Frontiers in Marine Science, 2023)
The entry into force of the Regional Comprehensive Economic Partnership (RCEP), the world’s largest free trade agreement, has injected new vitality into multilateralism and free trade, against a background of global economic and political instability. Its core concept is to liberalize and facilitate trade. Regulation of the shipping market warrants attention. Under the RCEP, the international shipping industry is characterized by a digital development trend in shipping supervision, continuous upgrading of shipping management and supervision capabilities, and more open and transparent shipping market supervision. However, in the process of implementing new rules for shipping market supervision, there are still some challenges, such as logistics risks and loopholes in shipping supply chains, insufficient coordination of shipping supervision among RCEP member countries, and an imperfect legal and regulatory system. This paper therefore suggests that under the RCEP, China should strengthen the anti-risk ability of shipping supply chains, promote coordinated supervision among member countries, strengthen environmental protection, and promote the coordination of digital supervision.